Serum Neudesin Levels in Gestational Diabetes Mellitus: A Potential Biomarker for Disease Prediction - Alaa Jumae Esmail; Areej Sh. Hameed; Ekhlas Khalid Hameed (Diyala Journal of Medicine, 2025)
Background: A common metabolic disorder during pregnancy is gestational diabetes mellitus (GDM). It is linked to insulin resistance and impaired glucose tolerance. The role of neudesin, a regulatory peptide hormone involved in glucose metabolism, as a potential biomarker for GDM remains unclear. Objectives: To assess Neudesin's predictive value for GDM and evaluate its correlation with insulin resistance indices and glycemic indicators. Patients and Methods: This case-control study was conducted in Baghdad, Iraq, from January to July 2025 at the Department of Chemistry, College of Science for Women, University of Baghdad, in collaboration with the Department of Obstetrics and Gynecology at Al-Yarmouk Teaching Hospital. Eighty healthy controls and 120 women with GDM were included. Serum Neudesin, fasting blood glucose (FBG), insulin, HOMA-IR, HbA1c, TyG index, and TyG-BMI index were evaluated. Results: Women with GDM had significantly higher serum Neudesin levels compared to controls (2.372 ± 0.36 ng/mL vs. 0.919 ± 0.156 ng/mL, p<0.001). Neudesin levels were positively correlated with BMI, FBG, HbA1c, insulin, HOMA-IR, and TyG indices (p<0.001). Logistic regression identified neudesin as an independent predictor for GDM. ROC analysis showed high diagnostic accuracy (AUC = 0.986), with a cut-off value of 1 1185 ng/ml, which yielded 100% sensitivity and 86.7% specificity. Conclusion: Circulating neudesin concentrations are markedly higher in individuals with GDM and show a strong correlation with the degree of insulin resistance and poor glycemic control. Neudesin may serve as a promising diagnostic biomarker and potential target for early identification and management of GDM. Keywords: Gestational diabetes mellitus, Neudesin, Insulin resistance, Biomarker.